Tolerance of milkfish (chanos-chanos) fry and hatirin stages to hydrogen peroxide and preliminary study on its efficacy againts amyloodinuim ocellatum infestation. - Cabillon, Nikko Alvin R. (College of Fisheries, University of the Philippines, 2014)
Milkfish (Chanos chanos) fry and hatirin (fingerling) stages were exposed to various concentrations of hydrogen peroxide (H2O2) to determine its tolerance to the chemical. Results show that milkfish fry and hatirin are highly tolerant to the chemical with a compound 96-h TL95 of 871.31 mg L-1H2O2 for milkfish fry. A 24-h treatment 100, 200, and 300 mg L-1 H2O2 was also concluded to test the efficacy of the chemical in eliminating Amyloodinium occelatum, a peridinean ectoparasitic dinoflagellate on milkfish fry. Although the treatments did not completely eradicate the parasite on the infected fry, the intensity of infection was reduced as compared to the untreated fish. Based on the results of this study, it is recommended to use 200 mg L-1 H2O2 for 24 h. However, further studies are recommended using low concentrations of H2O2 at extended periods of exposure as well as higher concentrations of the chemical at shorter exposure time.